Quels regards les enseignants de lycée professionnel portent-ils sur la poursuite d'études en première année de licence de leurs élèves ? - Charlotte Pourcelot
This article deals with a less known field in the educational system, that is to say, vocational high schools. The clear increase of BTEC National holders in French universities raises some questions among academics. This observation questions the forms used in order to improve the efficiency of training courses given before and after their BTEC National. It is therefore in that debate the exploratory research introduced in the article wishes to participate. In order to achieve this, 52 vocational high school teachers had been surveyed. The Multiple Correspondence Analysis (MCA) made it possible to divide the population into three classes.